The Role of Public Administration in Transport of Dangerous Goods - Martinović, Aleksandar (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Environmental protection is an area of social life, which is, among other things, decorated by norms of administrative law. The area of transport of dangerous goods, as an important part of the protection of the environment, is also regulated by administrative norms. The Ministry of Internal Affairs and Department for transport of dangerous goods as a body within the Ministry of Transport have a crucial role in the performance of state administration in the area of transport of dangerous goods.